2019
DOI: 10.7454/jki.v0i0.1073
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Minority Stress on Level of Depression among Thai LGBT Adults

Abstract: In the US, lesbian, gay, bisexual, and transgender (LGBT) individuals report higher rates of depression compared with heterosexual and cisgender persons. To date, little is known about the mental health of LGBT adults in Thailand. Here, we examined rates and correlates of depression among a volunteer sample of Thai LGBTs. Data were collected as part of a larger cross-sectional survey study. Standardized measures of sexual orientation and gender identity, stress, coping style, and minority stressors were comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 6 publications
3
24
0
Order By: Relevance
“…Moreover, Thai LGBT individuals report experiences of discrimination within their families, religious settings, schools, workplaces and when accessing governmental services (Suriyasarn, 2016; United Nations Development Programme & United States Agency for International Development, 2014; World Bank Group, 2018; Yadegarfard et al., 2014). A large body of research has established correlations between experiences of stigma, discrimination and poor mental health outcomes among members of stigmatized minority groups including racial/ethnic minorities (Wong et al., 2017), persons with stigmatized health conditions such as HIV/AIDS (Earnshaw et al., 2015) and LGBT populations (Kittiteerasack et al., 2020; Meyer, 2003; WHO, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Thai LGBT individuals report experiences of discrimination within their families, religious settings, schools, workplaces and when accessing governmental services (Suriyasarn, 2016; United Nations Development Programme & United States Agency for International Development, 2014; World Bank Group, 2018; Yadegarfard et al., 2014). A large body of research has established correlations between experiences of stigma, discrimination and poor mental health outcomes among members of stigmatized minority groups including racial/ethnic minorities (Wong et al., 2017), persons with stigmatized health conditions such as HIV/AIDS (Earnshaw et al., 2015) and LGBT populations (Kittiteerasack et al., 2020; Meyer, 2003; WHO, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, an emerging body of literature has documented high rates of depression among LGBT adults (40.3%; Kittiteerasack, Steffen, et al., 2020), gay men (47.1%; Pearkao, 2013), lesbians (27.7%; Boonkerd & Rungreangkulkij, 2014) and LGBT adolescents who have experienced school‐based bullying (22.6%; Mahidol University et al., 2014). However, rates of suicidality in Thai LGBT populations have not been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…We did not nd associations between other minority stressors and depressive symptoms. However, a study in Thailand suggested that experiences of victimization, discrimination, and identify concealment also predicted depression among sexual minorities [85]. More research is needed to con rm the relationship between various minority stressors and depressive symptoms in different cultural contexts.…”
Section: Discussionmentioning
confidence: 99%
“…We did not nd associations between other minority stressors and depressive symptoms. However, a study in Thailand suggested that experiences of victimization, discrimination, and identify concealment also predicted depression among sexual minorities [81]. More research is needed to con rm the relationship between various minority stressors and depressive symptoms in different cultural contexts.…”
Section: Discussionmentioning
confidence: 99%